Les « Malgré-Nous » et les « Malgré-Elles » : l’influence d’une catégorisation genrée sur la visibilité des témoignages des incorporé.e.s de force alsacien.ne.s dans la sphère publique pendant la Seconde Guerre mondiale - Marie Janot-Caminade (Genre & Histoire)
During the Second World War, Alsatian men were enlisted by force in the Wehrmacht while Alsatian women were sent to paramilitary units against their will. In the 1950s, the struggle for the political recognition of the incorporation by force begins. During this time, male and female groups disappear in favor of the mixed categories of « Malgré-Nous » and « Malgré-Elles » based on the gendered distinction between the front – seen as a male space – and the home front – considered female. The war experiences of each man or woman incorporated by force are redefined as transgressive or compliant to the gendered category to which they belong. This retrospective evaluation is decisive in the access to the public testimony by the men or women enlisted by force : having a "masculine" trajectory while being a woman is an asset while having a feminine trajectory when you are a man is a disadvantage.